Impact of Conditioning Regimen on Outcomes for Children with Acute Myeloid Leukemia Undergoing Transplantation in First Complete Remission. An Analysis on Behalf of the Pediatric Disease Working Party of the European Group for Blood and Marrow Transplantation - Lucchini, Giovanna; Labopin, Myriam; Beohou, Eric; Dalissier, Arnauld; Dalle, Jean Hughes; Cornish, Jacqueline; Zecca, Marco; Samarasinghe, Sujith; Gibson, Brenda; Locatelli, Franco; Bertrand, Yves; Abdel-Rahman, Fawzi; et al. (Biology of blood and marrow transplantation, 2017)
Hematopoietic stem cell transplantation (HSCT) represents the cornerstone of treatment in pediatric high-risk and relapsed acute myeloid leukemia (AML). The aim of the present study was to compare outcomes of pediatric patients with AML undergoing HSCT using 3 different conditioning regimens: total body irradiation (TBI) and cyclophosphamide (Cy); busulfan (Bu) and Cy; or Bu, Cy, and melphalan (Mel). In this retrospective study, registry data for patients > 2 and <18 years age undergoing matched allogeneic HSCT for AML in first complete remission (CR1) in 204 European Group for Blood and Marrow Transplantation centers between 2000 and 2010 were analyzed. Data were available for 631 patients; 458 patients received stem cells from a matched sibling donor and 173 from a matched unrelated donor. For 440 patients, bone marrow was used as stem cell source, and 191 patients received peripheral blood stem cells. One hundred nine patients received TBICy, 389 received BuCy, and 133 received BuCyMel as their preparatory regimen. Median follow-up was 55 months. Patients receiving BuCyMel showed a lower incidence of relapse at 5 years (14.7% versus 31.5% in BuCy versus 30% in TBICy, P < .01) and higher overall survival (OS) (76.6% versus 64% versus 64.5%, P = .04) and leukemia-free survival (LFS) (74.5% versus 58% versus 61.9%, P < .01), with a comparable nonrelapse mortality (NRM) (10.8% versus 10.5% versus 8.1%, P = .79). Acute graft-versus-host disease (GVHD) grades III and IV but not chronic GVHD, was higher in patients receiving BuCyMel. Older age at HSCT had an adverse impact on NRM and the use of peripheral blood as stem cell source was associated with increased chronic GVHD and NRM as well as lower LFS and OS. Among pediatric patients receiving HSCT for AML in CR1, the use of BuCyMel conditioning proved superior to TBICy and BuCy in reducing relapse and improving LFS.
Keywords: Busulfan; výsledek terapie; Recurrence; analýza přežití; busulfan; Male; retrospektivní studie; Child, Preschool; Antineoplastic Combined Chemotherapy Protocols; Adolescent; Cyclophosphamide; Transplantation, Homologous; Child; Europe; nemoc štěpu proti hostiteli; dítě; transplantace hematopoetických kmenových buněk; akutní myeloidní leukemie; mužské pohlaví; příprava pacienta k transplantaci; registrace; recidiva; melfalan; Survival Analysis; mladiství; Treatment Outcome; Evropa; homologní transplantace; předškolní dítě; Transplantation Conditioning; lidé; Leukemia, Myeloid, Acute; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; cyklofosfamid; Registries; celotělové ozáření; Retrospective Studies; Whole-Body Irradiation; Female; Melphalan; indukce remise; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Remission Induction